1999
DOI: 10.1192/bjp.175.4.375
|View full text |Cite
|
Sign up to set email alerts
|

Transcallosal inhibition and motor conduction studies in patients with schizophrenia using transcranial magnetic stimulation

Abstract: Magnetic motor conduction parameters are unaltered in schizophrenia, but transcallosal inhibition is significantly delayed and prolonged. This may indicate abnormal function of the corpus callosum in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
49
2
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 24 publications
11
49
2
2
Order By: Relevance
“…Reduced IHI 10 at rest has been a consistent finding in both medicated and unmedicated chronic SCZ. 29,37,44,69 In contrast, studies have also consistently found increased iSP in medicated and unmedicated chronic SCZ, 37,44,45,70,71 although not in first-degree relatives. 51 As IHI 10 and iSP are mediated by different neuronal populations, these divergent findings are likely to reflect separate pathological mechanisms.…”
Section: Interhemispheric Cortical Connectivitymentioning
confidence: 86%
“…Reduced IHI 10 at rest has been a consistent finding in both medicated and unmedicated chronic SCZ. 29,37,44,69 In contrast, studies have also consistently found increased iSP in medicated and unmedicated chronic SCZ, 37,44,45,70,71 although not in first-degree relatives. 51 As IHI 10 and iSP are mediated by different neuronal populations, these divergent findings are likely to reflect separate pathological mechanisms.…”
Section: Interhemispheric Cortical Connectivitymentioning
confidence: 86%
“…98 Relevant to the same issue is the preliminary finding of increased interhemispheric conduction time as estimated by the latency of the transcallosal inhibition of motor response of the first dorsal interossus muscle in 10 S patients. 100 Patients were found to have an interhemispheric conduction time of 15.3 vs 12.4 ms in controls. The duration of inhibition was also increased.…”
Section: Morphological Studiesmentioning
confidence: 99%
“…For example, four times more axons were counted electron microscopically than light microscopically in the cat. 100 Therefore, a decrease in the size of callosal axons in S could be mistakenly interpreted as a loss of axons. Furthermore, it is unclear if the counts should be corrected for brain size, because there are no robust reasons to expect that the number of callosal axons increases with brain size.…”
Section: Morphological Studiesmentioning
confidence: 99%
“…Patients with prominent negative symptoms often exhibit reduced activation in frontal brain regions, a state known as hypoactivation [3]. As normal control subjects [6]. It also reported longer transcallosal suppression of motor contractions in schizophrenia group compared with healthy subjects, although no change in the latency of effect was observed.…”
Section: Cortical Excitability and Inhibition Abnormalities In Schizomentioning
confidence: 97%